DEVELOPMENT OF TECHNOLOGY FOR PRODUCTION OF PLASTICIZERS ON THE BASIS OF TRIMETHYLOLPROPANE - A. Yu. Aleksandrov; E. L. Krasnykh; S. V. Levanova; I. L. Glazko; O. D. Lukin (Тонкие химические технологии)
Polyhydric alcohols - neopolyols and their derivatives due to the nature of the structure have a row of unique properties - high thermal stability, moisture resistance, chemical resistance and are widely used in the production of synthetic oils, resins, varnishes, surfactants and plasticizers. Esters of neopolyols with several ester groups have excellent characteristics at low temperatures, as well as high environmental friendliness, which meets modern requirements. The variation in the production of esters of neopolyols, alcohol and acid components in various combinations allows to obtain a wide range of products with different characteristics and consumer properties. Currently, neopolyol esters are not produced in Russia. However, the technical capabilities of the development of R-Oxo technology based on natural gas are not in doubt, which will allow in the near future to organize its own production of neopolyol esters for the production of high-tech materials. In the present work, the possibility of obtaining plasticizers based on trimethylolpropane esters and C2-C5 acids of various structures was investigated. Samples of 7 trimethylolpropane triesters were synthesized and their certain physicochemical properties were determined. It is shown that the most promising is the synthesis of a plasticizer using acetic acid. Conducted kinetic studies on the esterification of trimethylolpropane with acetic acid. A differential method was used to estimate the reaction rate from the initial consumption rates of acetic acid. The first orders of reaction are determined by alcohol and catalyst under the conditions studied; the value of the observed activation energy of the obtained reaction of the pseudo-second order, in the temperature range of 80-115 °C, was 57.9±8.1 kJ/mol. The results obtained allow us to recommend the conditions for the implementation of the process in the industry.